Effectiveness of a Total Meal Replacement Program (OPTIFAST Program) on Weight Loss: Results from the OPTIWIN Study. Issue 1 (13th November 2018) - Ard, Jamy D.; Lewis, Kristina H.; Rothberg, Amy; Auriemma, Anthony; Coburn, Sally L.; Cohen, Sarah S.; Loper, Judy; Matarese, Laura; Pories, Walter J.; Periman, Seletha
Abstract : Objective: The aim of this study was to test the effectiveness of the OPTIFAST program (OP), a total meal replacement dietary intervention, compared with a food‐based (FB) dietary plan for weight loss. Methods: Participants with BMI 30 to 55 kg/m 2, age 18 to 70 years old, were randomized to OP or FB dietary and lifestyle interventions for 26 weeks, followed by a weight‐maintenance phase. Outcomes were percent change in body weight (%WL) from baseline to weeks 26 and 52, associated changes in body composition (using dual energy x‐ray absorptiometry), and adverse events. Primary analysis used repeated‐measures multivariable linear mixed models to compare outcomes between groups in a modified intention‐to‐treat fashion (mITT). Results: A total of 273 participants (83% of randomized; 135 OP, 138 FB) made up the mITT population. Mean age was 47.1 ± 11.2 years; 82% were female and 71% non‐Hispanic white. Baseline BMI was 38.8 ± 5.9 kg/m 2 . At 26 weeks, OP %WL was 12.4% ± 0.6% versus 6.0% ± 0.6% in FB ( P < 0.001). At 52 weeks, OP %WL was 10.5% ± 0.6% versus 5.5% ± 0.6% in FB ( P < 0.001). Fat mass loss was greater for OP; lean mass loss was proportional to total weight loss. There was no difference in serious adverse event rates between groups. Conclusions: Compared with an FB approach, OP was more effective with greater sustained weight loss.